KONSEP TAZKIYAH AL-NAFS DALAM PENDIDIKAN ISLAM DAN RELEVANSINYA DENGAN TEORI SELF-ACTUALIZATION ABRAHAM MASLOW - Nurulhayati, Evi Luthfi; Mahawi; Ghani, Siti Jubaedah; Kurahman, Opik Taufik (As-Sulthan Journal of Education, 2025)
This study aims to analyze the concept of Tazkiyah al-Nafs in Islamic education and its relevance to Abraham Maslow's Self-Actualization theory. Using a qualitative approach with library research methods, this study examines primary and secondary sources related to both concepts. The results show that Tazkiyah al-Nafs which is the process of soul purification through the stages of takhalli (cleansing), tahalli (embellishment), and tajalli (illumination) has significant convergence with Maslow's hierarchy of needs toward self-actualization. Both concepts emphasize the importance of developing human potential gradually and holistically. However, the fundamental difference lies in their ultimate goals: while self-actualization focuses on the actualization of human potential, Tazkiyah al-Nafs leads to the achievement of ma'rifatullah (knowledge of God) and His pleasure as a transcendental goal. The findings of this study offer an integrative model that can enrich educational practices by combining the dimensions of Islamic spirituality and modern humanistic psychology.